Animals as non-human persons subject to law: New philosophical-legal paradigm? - Veliz Valencia, Yolange; Ramos Pico, Joseph (Frónesis, 2022)
The purpose of the scientific article is to reflect on animals as non-human persons subject to law, estimating the birth of a new philosophical-legal paradigm that arises from the recognition that the Constitution of the Republic of Ecuador makes of nature as holder of rights and the decisions that have been issued in the world in this regard, and that have taken as a basis the provisions of the Ecuadorian legal context. The research is of a critical-reflective nature where it tries to give answers to a set of unknowns that have guided the study. This analysis will seek more than finding answers, asking the right questions and reviewing to what extent respect for other living species is found in the axiological orders of man and determining whether "animalism" and "humanism" are compatible. The study recognizes the contributions of doctrine and specialized jurisprudence to unravel the need to consolidate this new paradigm that will definitely impact the way of assuming legal relationships. The conclusion is that this newest category of the non-human person who owns rights entails the construction of a legal approach or prototype that manages to honor the constitutional mandate that stands as a contribution to contemporary universal law, recognizing whether we are moving towards a higher moral conscience or we have simply filled ourselves with vague statements, which do not materialize in the essentials.